Diagnostic approach to elevated dd-cfDNA with reassuring EMB in heart transplantation - Bahniwal, Rupinder K.; Mehta, Aditya; Kennedy, Jamie L. W. (Frontiers in Transplantation, 2025)
Despite significant advances in organ preservation, surgical techniques, and immunosuppressive regimens, rejection continues to pose a major challenge in the care of heart transplant patients. Endomyocardial biopsy (EMB) remains the gold standard test for surveillance and diagnosis of rejection, but is limited by its invasiveness, interobserver variability, procedural risk, and cost thus prompting the widespread use of non-invasive biomarkers such as donor-derived cell-free DNA (dd-cfDNA). Due to its high negative predictive value, dd-cfDNA is often routinely used for surveillance of asymptomatic patients. However, it is a non-specific marker of allograft injury and elevated levels in the presence of a reassuring EMB creates a diagnostic dilemma. This review explores the pathophysiological basis and clinical utility of dd-cfDNA in monitoring of heart transplant recipients with particular focus on evaluation and management of discordant findings.